2014
DOI: 10.1186/1471-2458-14-504
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of stunting among children in Ghana

Abstract: BackgroundStunting, is a linear growth retardation, which results from inadequate intake of food over a long period of time that may be worsened by chronic illness. Over a long period of time, inadequate nutrition or its effects could result in stunting. This paper examines the correlates of stunting among children in Ghana using data from the 2008 Ghana Demographic and Health Survey (GDHS).MethodsThe paper uses data from the children recode file of the 2008 Demographic and Health Survey (DHS), a nationally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
67
3
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 10 publications
28
67
3
8
Order By: Relevance
“…On the other hand, females are culturally expected to be less active and stay at home with their mothers near food preparation. This finding is consistent with results from other cross-sectional studies carried out in Iran [16], Kenya [17], Indonesia [18], Tanzania [19] and Ghana [20]. …”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, females are culturally expected to be less active and stay at home with their mothers near food preparation. This finding is consistent with results from other cross-sectional studies carried out in Iran [16], Kenya [17], Indonesia [18], Tanzania [19] and Ghana [20]. …”
Section: Discussionsupporting
confidence: 93%
“…Also male children were revealed to be 2% more probable to suffer from fever relative to female children. This is similar to the results of Darteh et al (2014) who found stunting to be more among males than females. The explanation under diarrhoea still applies here.…”
Section: Regression Resultssupporting
confidence: 91%
“…Also on average, Muslim children and male children were 7% and 4% more probable to have diarrhoea relative to those from Spiritualist/Traditional/No religion faiths and female children respectively. The findings of male children is in line with that of Darteh et al (2014) who revealed stunting to be higher among males than females in Ghana. This can be due to the perception of people that male children are naturally stronger relative to female children and hence may not be given much care which might make them more susceptible to diseases.…”
Section: Regression Resultssupporting
confidence: 88%
“…Male children were also more likely to be stunted compared to female children. This relationship has been reported in the literature from developing countries including Ghana [14,26], Tanzania [27], Ethiopia [24], Cambodia [3] and India [28]. In spite of this widespread identification of the male susceptibility to stunting, the exact factors underlying it have yet to be well understood [14] but likely to be biological [29].…”
Section: Discussionmentioning
confidence: 86%